ANTI-BIOFILM EFFICACY OF PLECTRANTHUS AMBOINICUS AGAINST STREPTOCOCCUS PYOGENES ISOLATED FROM PHARYNGITIS PATIENTS - K, Manimekalai; P, Srinivasan; J, Dineshbabu; G, Guna; D, Teepica Priya Darsini (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The objective of the study was to evaluate the anti-biofilm efficacy of Indian medicinal plant Plectranthus amboinicus extracts against the biofilm forming Streptococcus pyogenes isolated from pharyngitis patients. Methods: The plant extracts (methanol and ethyl acetate) were screened for their preliminary phytochemical components. The solvent extract with higher phytochemical yield was subjected to quantitative analysis using the Gas Chromatography-Mass Spectrometry (GC-MS) technique. In vitro analysis of the anti-biofilm study was performed using the Minimal Inhibitory Concentration (MIC) assay, biofilm inhibitory concentration assay, growth curve analysis, anti-bacterial activity, and light microscopy analysis. Results: The methanol extract showed the highest phytochemical content. GC-MS analysis of the methanol extract showed a total of thirty two phyto compounds among which most of the compounds were medicinally important. MIC assay showed that the inhibition of test pathogens was at an average concentration of 2 mg/ml. The agar well diffusion method elucidated that at sub-MIC the methanol and ethyl acetate extracts did not inhibit the growth of the test pathogen. Growth curve analysis was carried out at the concentration sub-MIC, in which the solvent extracts did not show any significant inhibition on the planktonic cells, whereas the biofilms of the test pathogens were significantly reduced and were dose dependent at subMIC levels as confirmed by the light microscopic analysis. Conclusion: These preliminary results indicated that the methanol extract of P. amboinicus leaves consisted of pharmacologically active components and could be used as an anti-biofilm agent at minimal concentrations thereby successful preventing the formation of biofilms. Keywords: Plectranthus amboinicus, GC-MS, Anti-biofilm activity, Light microscopy, S. pyogenes.